Text of the general agreement (GATT GenevaCH, 1986)
Contains complete text of the General Agreement together with all ammendments which have become effective since its entry into force on January 1 1948. Two appendices provide the legal sources of the various provisions of the agreement and a key to the abbreviated titles used in section one of this monograph.
DC